Challenging the Frontiers of Poverty Reduction (CFPR) - targeting the ultrapoor- targeting social constraints: Volume 1, 2002 - BRAC (© BRAC, 2016)
1. Overview proposal 2. Special investment programme for the ultra poor 3. Employment and enterprise development training 4. Social development programme 5. Essential health care programme 6. References.